Predictors of Symptomatic Hemorrhage After Endovascular Treatment for Anterior Circulation Occlusions: Turkish Endovascular Stroke Registry - Sengeze, Nihat; Ozdemir, Ozcan; Eren, Alper; Aykac, Ozlem; Gencer, Elif Sarionder; Giray, Semih; Karaibrahimoglu, Adnan (Sage Publications Inc, 2022)
We evaluated the predictive factors of symptomatic intracranial hemorrhage (SICH) in endovascular treatment of stroke. We included 975 ischemic stroke patients with anterior circulation occlusion. Patients that had hemorrhage and an increase of >= 4 points in their National Institutes of Health Stroke Scale (NIHSS) after the treatment were considered as SICH. The mean age of patients was 65.2 +/- 13.1 years and 469 (48.1%) were women. The median NIHSS was 16 (13-18) and Alberta Stroke Program Early CT 9 (8-10). In 420 patients (43.1%), modified Rankin Scale was favorable (0-2) and mortality was observed in 234 (24%) patients at the end of the third month. Patients with high diastolic blood pressure (P<.05) had significantly higher SICH. SICH was significantly higher in those with high NIHSS scores (P<.001), high blood glucose (P<.001), and leukocyte count at admission (P<.05). Diabetes mellitus (DM) (OR 1.90; P<.001), NIHSS (OR 1.07; P<.05), adjuvant intra-arterial thrombolytic therapy (IA-rtPA) (OR, 1.60; P<.05), and puncture-recanalization time (OR 1.01; P<.05) were independent factors of SICH. Higher baseline NIHSS score, longer procedure time, multiple thrombectomy maneuvers, administration of IA-rtPA, and the history of DM are independent predictors of SICH in anterior circulation occlusion.
Keywords: stroke; anterior circulation occlusion; endovascular therapy; symptomatic hemorrhage